Windows Server 2003 Networking Recipes A Problem-Solution Approach - Allen, Robbie; Hunter, Beau; Dinerman, Brad (Apress : Imprint: Apress, 2006)
Windows Server 2003 Networking Recipes is ideal for network managers and Windows Server 2003 system administrators responsible for setting up and running computers and networks. Think of this book as the comprehensive, task-based guide to installing, deploying, and configuring the various networking protocols and services supported by Windows Server 2003 and the only book you'll need. You'll find hundreds of quick reference solutions. And the featured recipes are all based on the first-hand experiences of the authors. You can rest assured that this book is written by a team of leading experts in Windows administration.